ALCOHOLISM: AN UNDERSTANDING OF THE NEUROSYSTEMIC APPROACH INVOLVEMENT WITH AYURVEDA - Lekharu, *Sikha; Basumatary, Khagen (International Journal of Ayurveda and Pharma Research, 2017)
Alcohol consumption is an integral part of daily life in many societies. In general it is related to lower health status, more health problems and a shorter life expectancy. being a social stigma, it ranks among the top 5 risk factor of diseases. Ayurveda considers addiction under the topic of Madatya, which means intoxication. Madatya is the state or symptoms that arise due to continuous use or a high dose of substances that are intoxicating. According to Ayurveda, Madya (alcohol/drug) is the complete opposite of ojas (source of energy) which is a prerequisite for good health and wellness. Madya finishes Oja in the body and when a person reaches that stage, he experiences the symptoms of Madya. According to modern medicine there are four stages of addiction – Acute intoxication, withdrawal symptoms, drug dependence and finally drug abuse. The stage of Madatya can be compared to the 3rd and 4th stage. In Charak Siddhisthana it says that the Hridaya present in Shira effects the Gyanendriya and Karmendriya. and this Shira is effected by the Madya which disrupts the Ojha. Going through various research study it has been proved that alcohol leads to Neurodegeneration, which changes in the neuronal function viz reward circuits and neurotransmitter system particularly dopamine system, opiod system, gamma- aminobutyric acid system acid system, glutamate system etc. Thus an humble attempt has been made to understand the neurosystem involvement and degeneration caused by alcohol (Madya) by both Ayurveda and modern science.